Financing Politics in Indonesia - Savirani, Amalinda; Mas'oed, Mohtar (PCD Journal, 2011)
This paper aims to map out practices of political financing in Indonesia from the political to the socio-historical perspective. Arguing about the party financing and the corruption of politicians and the parties, this paper also proposes about strategies at the individual level for performing financing politics, as well as factors that help to explain their performance. It compares cases in three different periods of Indonesian history: the post-independence, the Suharto (New Order) era, and reformasi after the fall of Suharto in 1998. This paper discusses and analyses the financing politics belonging to the political and socio-historical perspective, the issue of financing politics, the results of mapping students theses from three universities in Java together with relevant papers by LIPI (the Indonesian Sciences Institute), and directly presents three case studies of individual performing financing politics. Two of the case studies concern with politicians from the post-independence and Suharto era, while the third concerns a member of the city of Solo's local parliament. This paper shows how financing politics would be no longer relevant, as the cultural capital, political capital, and social capital also may contribute in supporting one's political career.